INFRASTRUKTUR DAN PERTUMBUHAN EKONOMI KABUPATEN DAN KOTA JAWA BARAT - Wardhana, Adhitya; Kharisma, Bayu; Hanifah, Hani (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.04.TAHUN 2020DO - 10.24843/EEB.2020.v09.i04.p01, 2020)
This research discusses the infrastructure that affects district / city economic growth in West Java. The infrastructure studied is in the form of physical infrastructure such as the length of the road, public facilities and the number of schools. These three infrastructures tend to increase labor productivity which can increase economic growth. Then the other variable in this study is the labor variable (control) that affects economic growth. The research model uses the Generalized Least Square (GLS) data panel model with the scope of 26 regencies / cities in West Java for the period 2011-2018. Infrastructure variables such as road length, number of junior high schools and public facilities significantly influence the economic growth of the Regency / City of West Java. Then the labor variable significantly affects the economic growth of the Regency / City in West Java. The public facilities variable is the dependent variable that most influences economic growth in West Java.